Application of Genetic Algorithms for Estimation of Impedance Parameters of Two-Terminal Networks - Janeiro, Fernando M. (2010)
A new procedure to estimate the value of the individual components of a two-terminal impedance network is presented. It is based on the application of genetic algorithms to the spectral fitting of the impedances’ model. The expanded uncertainty of the estimated parameters is obtained through simulations and the algorithm is also applied to the measured frequency response of two impedance networks. Partial knowledge of spectral response is shown to be sufficient for the correct estimation of the individual component parameters.